Effects of Powdered Salmon Roe Processing Liquid on Enhancing the Palatability of Tuna By-Product Meal-Based Diets in Greater Amberjack (Seriola dumerili) - Amal Biswas; Ryoma Maruyama; Satoshi Okimura; Hiroshi Fushimi; Hiroya Sato; Yoshihiro Kakinuma; Tomoki Honryo; Hideki Tanaka (Fishes)
A two-factorial experiment was conducted to evaluate the potential for improving the palatability and utilization of tuna by-product meal (TBM) as a replacement for fish meal (FM) via supplementing the diet of juvenile greater amberjack (Seriola dumerili) with powdered salmon roe liquid (PSRL). FM protein in the control diet (C) was partially replaced with TBM at levels of 25% (T25R0) and 40% (T40R0). PSRL was then added at 5% and 10% to both the T25R0 and T40R0 diets, resulting in the formulations T25R5, T25R10, T40R5, and T40R10. After a 6-week rearing period, during which groups of 30 juveniles (mean initial weight of approximately 1.7 g) were stocked in 500 L tanks, there were no significant differences in the final mean weight, weight gain, or specific growth rate among fish fed diets C, T25R0, and T25R5. However, the other experimental diets showed significantly lower values compared to the C diet (p < 0.05). PSRL supplementation did not significantly enhance either palatability or feeding rate in TBM-based diets (p > 0.05). Two-way ANOVA indicated that only FM replacement with TBM had a significant effect on the growth parameters mentioned above (p < 0.05). A significantly lower whole-body crude lipid content was observed in all test diets compared to that in the C diet, resulting in significantly lower lipid retention efficiency in all test groups except T25R5 and T25R10 (p < 0.05). These results suggest that 25% of FM protein can be replaced with TBM protein in the diet of juvenile greater amberjack, but PSRL does not effectively address the palatability issues associated with TBM-based diets.